(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s ((3eMeO GdJgGej Hf CMeO Hf eMeO GdJhfSj GdCfOdSj GdQHGWj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj MHGfj HGdCUZQjf GdbdH hGddSGf s
(3BNQgG (B:s
(3Ef GdaNGQ hGdYdG EQKc ef Ohf GdedG Je GdcJGH fSNoG HMeO Gddg s
(3JJab aj ChdgG hBNQgG eY GdfSNI GdKGfjI eY GNJdGa aj HYV GdCdaGXs
(3fSNI SGHYIs
(3hHgG fXGe GdJYbjHIs
(3hjdjgG efXheI aj GdCOhjI hGdhUaGJ GdWHjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdCOHs